THE EFFECTIVENESS OF BEHAVIORAL CONTRACT GROUP COUNSELING IN IMPROVING THE DISCIPLINE OF 11TH-GRADE STUDENTS AT PILANGKENCENG STATE HIGH SCHOOL, MADIUN REGENCY - Nur Sawaludin; Asroful Kadafi; Ratih Christiana (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to determine the effectiveness of group counseling using the behavioral contract technique in improving the discipline of eleventh-grade students at Pilangkenceng State Senior High School, Madiun Regency. The problem of low student discipline often becomes an obstacle in the learning process, so a systematic and structured approach is needed to improve student discipline. In this study, the method used was an experimental study with a pre-test and post-test design involving two groups: an experimental group that was given a group counseling intervention with the behavioral contract technique and a control group that did not receive the intervention. Data collection techniques were carried out through observation, interviews, and student discipline questionnaires that measured aspects of discipline such as tardiness, attendance, and compliance with school rules. The results showed that there was a significant increase in discipline in the experimental group after being given the intervention compared to the control group. This finding proves that the application of the behavioral contract technique in group counseling can be an effective alternative in improving student discipline. Therefore, it is recommended that schools consider implementing this technique as part of their character building and student discipline program